Learning efficacy between religious and public school students:A comparative study. - Md. Sawari, Siti Salwa; Ghazali, Mohd Al Ikhsan; Mansor, Norwati (Universiti Sains Malaysia, 2014)
Learning efficacy functions to increase the desire of learning through mediations of motivations and confidence This present study was designed to investigate two main objectives. First, it examines the level of learning efficacy among selected secondary students.